2015
DOI: 10.1111/etp.12091
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of studies on dentinal radicular microcracks in endodontics: methodological issues, contemporary concepts, and future perspectives

Abstract: The dentinal radicular microcrack is a difficult clinical problem to diagnose and treat, and it is one of the most common reasons for tooth extraction. These microcracks start in the radicular dentin, and laboratory studies have linked crack formation to some routine endodontic procedures, namely root canal preparation, obturation, and retreatment. Most of these studies were performed using destructive methods, such as the sectioning technique, previously developed for the study of the internal anatomy of teet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
109
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 155 publications
1
109
3
5
Order By: Relevance
“…Earlier in vitro experimentation showed that VRFs may occur under spreader loads of 1.5 kg (33), whereas dentinal defects and craze lines can occur after lateral compaction (13). Although it has not been proven that lateral compaction can be a trigger for VRFs, it has been reported that lateral compaction is the most used technique of obturation in endodontically treated teeth with VRFs (34). However, the current study did not compare the influence of different root canal filling techniques on VRFs.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier in vitro experimentation showed that VRFs may occur under spreader loads of 1.5 kg (33), whereas dentinal defects and craze lines can occur after lateral compaction (13). Although it has not been proven that lateral compaction can be a trigger for VRFs, it has been reported that lateral compaction is the most used technique of obturation in endodontically treated teeth with VRFs (34). However, the current study did not compare the influence of different root canal filling techniques on VRFs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the destructive nature of sectioning methods has several drawbacks such as evaluation of only 3-4 specific levels of the specimen with the chance of missing microcracks in other regions of the root. In summary, several authors concluded that root-sectioning methods and direct observation of root slices by optical microscopy present meaningful disadvantages that reduce the overall reliability of this experimental model (4,9,13,28). In summary, several authors concluded that root-sectioning methods and direct observation of root slices by optical microscopy present meaningful disadvantages that reduce the overall reliability of this experimental model (4,9,13,28).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, an unpredictable quantity of undetected preoperative microcracks may be a reason for different results when comparing these studies (14). This technique is unable to detect craze lines and defects throughout the longitudinal axis of the root (4,13), and light reflections on the resected root surface may lead to false-positive results (27). This technique is unable to detect craze lines and defects throughout the longitudinal axis of the root (4,13), and light reflections on the resected root surface may lead to false-positive results (27).…”
Section: Discussionmentioning
confidence: 99%
“…Vertikal kök kırıkları, endodontik tedavili dişlerde başarısızlığa neden olan önemli faktörler arasındadır 1,2,3 . Kök kanal şekillendirmesi sırasında kök yüzeyinde meydana gelen mikroçatlaklar, kök kırıklarının oluşmasında rol oynamaktadır 4,5 .…”
Section: Introductionunclassified